2022
DOI: 10.1021/acssuschemeng.2c04899
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Organic–Inorganic Polyphosphoramide-Halloysite Nanohybrids for Thermally Stable and Fire-Resistant Polylactide

Abstract: Biodegradable and renewable polylactide (PLA) exhibits excellent mechanical properties but is prone to high flammability, limiting its application to textiles, electronics, and packaging. In PLA, polyphosphoramides have shown their exceptional fire-retardant properties, but their existing synthesis methods often involve toxic solvents. Despite high efficiency, recently, polyphosphoramides prepared via green synthesis led to a reduced thermal stability of PLA. Herein, we report a series of organic−inorganic hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…23 Feng et al synthesized organic−inorganic hybridized polyphosphoramide-halloysite nanotube nanohybrids (DM−OH n ) and showed that the addition of only 1.5 wt % DM−OH 16 enabled PLA to achieve the UL-94 V-0 rating. 24 Xu et al designed a new phosphaphenanthrene-benzimidazole derivative (D-AB), which resulted in a satisfactory UL-94 V-0 rating and high limiting oxygen index (LOI) of 30.5% for PLA with 5 wt % content of D-AB, as well as improved its melt-dripping behavior. 25 These FRs can effectively improve the flame retardancy of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…23 Feng et al synthesized organic−inorganic hybridized polyphosphoramide-halloysite nanotube nanohybrids (DM−OH n ) and showed that the addition of only 1.5 wt % DM−OH 16 enabled PLA to achieve the UL-94 V-0 rating. 24 Xu et al designed a new phosphaphenanthrene-benzimidazole derivative (D-AB), which resulted in a satisfactory UL-94 V-0 rating and high limiting oxygen index (LOI) of 30.5% for PLA with 5 wt % content of D-AB, as well as improved its melt-dripping behavior. 25 These FRs can effectively improve the flame retardancy of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…[64] More recently, Feng et al reported a one-step solvent-free approach for synthesizing polyphosphoramide fire retardants that endow PLA with excellent flame retardancy. [12][13][14] For this green yet facile synthesis strategy, no post-treatment is involved, including products purification and solvent waste disposal. For these eco-friendly advantages, a growing number of attempts focusing on green solvents or solvents-free methods for FRs synthesis should be encouraged, expediting the real-world application of these green approaches in industry.…”
Section:  Chemical Synthesismentioning
confidence: 99%
“…Another example is methanol formed in the green synthesis of polyphosphoramides based on amine ester exchange reaction. [12][13][14] The only by-product methanol can be collected via vacuum pumping system and reused. Thus, it is advisable to make more efforts to convert the chemical waste to resources.…”
Section:  Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated polyester (UP) is widely used in transportation, building materials, and electrical insulation and has become a valuable engineering resin because of its superior mechanical resistance, excellent electrical insulation, and ease of processing. Since neat UP is flammable, its applications are greatly limited, thus leading to an increasing demand for flame-retardant UP. Incorporating flame-retardant additives into the UP matrix is a convenient way to obtain flame-retardant UP materials. Traditionally, halogenated flame retardants were widely used; however, with an increasing awareness of environmental protection, halogen-free flame retardants have become increasingly popular for UP, including two-dimensional materials, intumescent flame retardants, , and organophosphorus flame retardants. Due to their high efficacy, low toxicity, and good compatibility with the polymer matrix, organophosphorus flame retardants have become viable flame retardants. Zhao et al synthesized a poly­(hydroxyphenyl imino methyl phenol spirocyclic pentaerythritol diphosphonate), and its addition into UP led to a limiting oxygen index (LOI) value of 28.2% and a UL 94 V-0 rating in the resultant flame-retardant UP as well as a sharp decrease in the peak heat release rate (PHRR) by 60%, demonstrating a dramatic enhancement in flame retardancy. Liquid organophosphorus flame retardants have some shortcomings, even though previous studies have shown that they can enhance flame retardancy.…”
Section: Introductionmentioning
confidence: 99%